Analisis Hambatan Penyedia Operasional Kapal Time Charter Crew Boat - Ganesha Putra Ramadhani; Rizqi Aini R; Akhmad Kasan Gupron (BADAN PENERBIT STIEPARI PRESS, 2025)
PT Ekalya Purnamasari operates in the maritime services sector, primarily providing time charter crew boats to support maritime industry operations. However, in practice, vessel operations often encounter issues that disrupt performance and service efficiency. These obstacles can delay operations, increase maintenance costs, and result in contract breaches. Therefore, the objective of this study is to identify the key factors that contribute to the inefficiency of vessel operations. This research employs a qualitative approach involving observation, documentation, and interviews, with data analysis conducted using the Fishbone diagram (5M+1E). The findings reveal that the two main constraints hindering vessel operations are technical issues and human resource limitations. The shortage of crew members and delays in crew rotation prevent vessels from operating on schedule. Additionally, unplanned maintenance and main engine failures contribute to operational delays. Furthermore, inefficiencies are exacerbated by issues in spare parts procurement and a lack of coordination between departments. This study provides an in-depth understanding of the factors that hinder the operational efficiency of PT Ekalya Purnamasari’s time charter crew boats. These insights can be utilized by the company to develop strategic measures for improving its operational efficiency.